Claridge's Hotel puts out registration of trade mark by candle maker Claridge Candles. (6th November 2019) - Shaw, John
Abstract: Claridge's Hotel Limited v (1) Claridge Candles Limited (2) Denise Shepherd [2019] EWHC 2003 (IPEC), Claim No: IP-2018-000160, 29 July 2019 Claridge's Hotel was successful in its claim to prevent the sale of CLARIDGE branded candles.